Bahasa Arab sebagai Fondasi Epistemologis dalam Formulasi Kaidah-Kaidah Fikih - Sumarjoko, Sumarjoko; Ulfa, Hidayatun (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2025)
This study examines the epistemological role of the Arabic language in the formulation of al-qawāʿid al-fiqiyyah (legal maxims) and its implications for the validity and authority of Islamic law. The central inquiry addresses the extent to which Arabic functions not merely as a medium of expression, but as a methodological structure in the construction of legal maxims. Employing a qualitative library-based approach, this research applies linguistic and normative analysis to explore the relationship between the Qur’anic and Prophetic texts and the formulation of legal maxims. The findings demonstrate that the disciplines of naḥw (syntax) and ṣarf (morphology) play a crucial role in preserving semantic precision within the primary legal sources, which, through the process of takhrīj al-aḥkām (derivation of rulings) and systematic abstraction, give rise to universal legal principles (al-aḥkām al-kulliyyah) articulated as legal maxims. The concise yet semantically dense structure of Arabic enables the formulation of comprehensive principles encompassing diverse subsidiary legal cases. The Arabic redaction of al-qawāʿid al-fiqiyyah constitutes an integral component of their normative construction and legal legitimacy, while translation functions primarily as an explanatory instrument within pedagogical contexts.